2023
DOI: 10.29333/iejme/12649
|View full text |Cite
|
Sign up to set email alerts
|

Social and socio-mathematical norms constructed by teachers in classes through the development of noticing skills

Abstract: This paper examined how teachers’ noticing skill affects the social and socio-mathematical norms they construct in the classroom. The study was carried out with four mathematics teachers working at a secondary school in the eastern regions of Turkey. A case study among qualitative research methods was used. The data of the research were collected via videotaped lessons. The data obtained from teachers’ classroom practices were evaluated performing descriptive and content analysis. Research findings show that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Attending to critical events within classroom environment is an integral part of noticing (Ozdemir-Baki & Kilicoglu, 2023;van Es & Sherin, 2002). A significant difference was found between the pre-test and post-test scores of the teachers regarding the attending dimension.…”
Section: Discussionmentioning
confidence: 91%
“…Attending to critical events within classroom environment is an integral part of noticing (Ozdemir-Baki & Kilicoglu, 2023;van Es & Sherin, 2002). A significant difference was found between the pre-test and post-test scores of the teachers regarding the attending dimension.…”
Section: Discussionmentioning
confidence: 91%
“…Earlier literature on social and sociomathematical norms focused on, among others, their development (McClain & Cobb, 2001), establishing patterns of interactions (Roy et al, 2014) and how the norms are identified (Güven & Dede, 2017) in mathematics classrooms. Recent studies link sociomathematical norms with mathematical learning and teaching experiences like self-efficacy (Apsari et al, 2020), early numeracy learning (Morrison et al, 2021), abilities in problem-solving (Dini & Maarif, 2022), mathematical process skills (Gülburnu & Gürbüz, 2022), mathematical modelling activities (Yenmez & Erbaş, 2023), and teacher noticing (Baki & Kilicoglu, 2023). This article follows these trends and explores how transforming existing sociomathematical norms enhances learners' proficiency in mathematics.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Originally, Yackel and Cobb concentrated on analyzing mathematical discussions -for example, explanation, justification, and argumentation -but sociomathematical norms also steer learners' other mathematical activities such as participation in smallgroup interactions (Yackel, Cobb, & Wood, 1991). It has also been noticed that sociomathematical norms and social norms are related to one another (Ozdemir Baki & Kilicoglu, 2023).…”
Section: Introductionmentioning
confidence: 99%